2015
DOI: 10.1038/nrgastro.2015.107
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of noncoeliac gluten sensitivity

Abstract: The past 5 years have seen an increase in the use of a gluten-free diet outside a diagnosis of coeliac disease or IgE-mediated wheat allergy. This trend has led to the identification of a new clinical entity termed noncoeliac gluten sensitivity (NCGS). In this Review, we discuss the evidence for NCGS as demonstrated by the results of double-blind, placebo-controlled dietary rechallenge studies. Furthermore, the characteristic phenotype of individuals with NCGS is described as well as the symptom manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 114 publications
0
70
0
3
Order By: Relevance
“…It has been suggested that in NCGS gluten-related peptides enter the systemic circulation and cause extraintestinal manifestations such as ataxia, neuropathy and encephalopathy [108]. Moreover, it has been proposed that gluten causes depression, anxiety, autism and schizophrenia in patients with NCGS [109], and also reported that psychosis might be a manifestation of NCGS [110].…”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…It has been suggested that in NCGS gluten-related peptides enter the systemic circulation and cause extraintestinal manifestations such as ataxia, neuropathy and encephalopathy [108]. Moreover, it has been proposed that gluten causes depression, anxiety, autism and schizophrenia in patients with NCGS [109], and also reported that psychosis might be a manifestation of NCGS [110].…”
Section: Gluten Intolerance Pathogenesismentioning
confidence: 99%
“…Uncertainty exists of the exact component in a gluten‐containing diet responsible for symptom induction. There is difficulty in separating gluten‐mediated effects from other components present in wheat, eg, fructan (FODMAP) and amylase trypsin inhibitors, as well as difficulty in ensuring adequate exclusion of celiac disease . This has resulted in various names for the condition such as non‐celiac gluten sensitivity, or non‐celiac wheat sensitivity.…”
Section: Dietary Therapies For the Treatment Of Irritable Bowel Syndromementioning
confidence: 99%
“…These latter data challenge the concept of NCGS. Whether NCGS represents a separate disease entity apart from IBS, and whether other constituents of gluten-rich food such as amylase-trypsin inhibitors are involved in symptom generation in these patients, remains to be determined [50]. FODMAPs (fermentable oligo-, di-, and monosaccharides and polyols) are poorly absorbed short-chain carbohydrates, which undergo fermentation in the colon, thereby increasing the fecal water content, gas production and distention [51].…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%